PENGETAHUAN GURU TENTANG MEDIA POP-UP DALAM PEMBELAJARAN DI TK SE-KABUPATEN KUBU RAYA - Miftahul Adawiyah; Muhamad Ali; Dian Miranda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research aims to find out the level of knowledge of teachers about Pop-Up media in learning in kindergarten in Kubu Raya Regency. The research method used is Survey with quantitative research form. The data source in this study is a kindergarten teacher in Kubu Raya district which amounted to 156. the data is in the form of respondents' answers from questionnaires filled in through the goggle form link. This study uses quantitative descriptive statitstic techniques that are poured in the form of percentages. The results of the study with a total of 156 respondents showed that 71.2% of teachers know the meaning of Pop-Up media, 92.3% of teachers know the characteristics of PopUp media, 42.9% of teachers know how to use Pop-Up media, 47.4% of teachers know the types of Pop-Up media, 49.4% of teachers know the pop-up media section, and 48.1% of teachers know the advantages and disadvantages of Pop-Up media in learning in kindergarten in Kubu Raya Regency. Thus, the level of teacher knowledge about PopUp media in learning in Kindergartens in Kubu Raya Regency as a whole falls into the category of sufficient. 44.2% of "good" categories 46.2% of "enough" categories and 9.6% of "less" categories.Keywords: Teacher Knowledge About Pop-Up Media